Assessment of mechanical response of natural asphalt using ambient temperature samples from Caquetá, Colombia - Moreno-Anselmi, Luis Angel; Reyes-Ortiz, Óscar Javier; Ruíz-Acero, Johana Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The aim of this research was to evaluate the mechanical behavior of natural asphalt by making samples at ambient temperature. It was made a material characterization testing, using quantitative extraction of bitumen to know the asphalt content in the material. Then, it was proceeded to fabricate samples with pure natural asphalt in the gyratory compactor, and finally, samples were assayed by indirect tensile strength test in dry and wet conditions to know the viability of its use in tertiary roads without being subjected to high temperatures in manufacturing and mixing. The main result is evidence that the specimens fabricated at room temperature have very low resistance, so it is necessary to test the addition of stone aggregates at the same temperature and asphalt emulsions.